The most heat‐resistant conidia observed to date are formed by distinct strains of Paecilomyces variotii. (24th October 2019) - van den Brule, Tom; Punt, Maarten; Teertstra, Wieke; Houbraken, Jos; Wösten, Han; Dijksterhuis, Jan
Summary: Fungi colonize habitats by means of spores. These cells are stress‐resistant compared with growing fungal cells. Fungal conidia, asexual spores, formed by cosmopolitan fungal genera like Penicillium, Aspergillus and Peacilomyces are dispersed by air. They are present in places where food products are stored and as a result, they cause food spoilage. Here, we determined the heterogeneity of heat resistance of conidia between and within strains of Paecilomyces variotii, a spoiler of foods such as margarine, fruit juices, canned fruits and non‐carbonized sodas. Out of 108 strains, 31 isolates showed a conidial survival >10% after a 10‐min‐heat treatment at 59°C. Three strains with different conidial heat resistance were selected for further phenotyping. Conidia of DTO 212‐C5 and DTO 032‐I3 showed 0.3% and 2.6% survival in the screening respectively, while survival of DTO 217‐A2 conidia was >10%. The decimal reduction times of these strains at 60°C ( D 60 value) were 3.7 ± 0.08, 5.5 ± 0.35 and 22.9 ± 2.00 min respectively. Further in‐depth analysis revealed that the three strains showed differences in morphology, spore size distributions, compatible solute compositions and growth under salt stress. Conidia of DTO 217‐A2 are the most heat‐resistant reported so far. The ecological consequences of this heterogeneity of resistance, including food spoilage, are discussed.